Ilustración y progreso en David Hume - Rosales Rodríguez, Amán (Logos. Anales del Seminario de Metafísica, 2005)
The relationship between Enlightenment and progress in David Hume is presented and discussed in the context of the Scottish Enlightenment. It is asserted that Hume’s thoughts on progress, although similar to those exposed by some of his contemporaries, are characterized by a sober conception of human action on history. Hume’s political and social philosophy proposes an interesting critical philosophy of history and progress, avoiding the undesirable extremes of naïveté and pessimism
Keywords: Enlightenment; progress; Hume; history; skepticism